2010
DOI: 10.1055/s-0030-1248941
|View full text |Cite
|
Sign up to set email alerts
|

Is It Useful to Measure C-Reactive Protein and Leukocytes in Patients with Prelabor Rupture of Membranes?

Abstract: Neonatal infection is the main complication of prelabor rupture of membranes (PROM). We studied the accuracy of measuring C-reactive protein (CRP) and leukocytes in maternal serum to predict neonatal infection. We performed a retrospective cohort study in two hospitals in the Netherlands between 2003 and 2006. We included consecutive women hospitalized for PROM. In both hospitals, CRP and leukocytes were measured routinely in maternal serum every 2 days until delivery. End points considered were clinical neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…Nevertheless, in the current study the AUC for the maternal serum CRP was relatively small (95% CI, 0.600-0.800) and the likelihood ratio was 1.84, which suggests that the usefulness of serum CRP alone as a predictor of early-onset neonatal sepsis is limited. These findings are in agreement with the recent study by van der Heyden et al (24). …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, in the current study the AUC for the maternal serum CRP was relatively small (95% CI, 0.600-0.800) and the likelihood ratio was 1.84, which suggests that the usefulness of serum CRP alone as a predictor of early-onset neonatal sepsis is limited. These findings are in agreement with the recent study by van der Heyden et al (24). …”
Section: Discussionsupporting
confidence: 94%
“…A number of studies have assessed the relationship between early-onset neonatal sepsis and the maternal serum CRP level; some studies have demonstrated a significant association (12, 23, 24), while other studies have failed to do so (25, 26). This discrepancy among studies is probably attributable, in part, to a wide variety of time intervals between CRP measurement and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…A simple and more repeatable method would be assessment of maternal serum inflammation markers: however there is still no consensus on the ideal marker as far as sensitivity and specificity is concerned [12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of maternal CRP as a marker of fetal intrauterine infection in pPROM has been investigated by numerous authors, but results are still controversial [10,11,12,13,14,15] due to bias linked to different methodologies and study models.…”
Section: Introductionmentioning
confidence: 99%
“…Of them, maternal CRP has been reported to be valuable for early detection of neonatal sepsis 13,14. Conflicting results on use of maternal CRP in prediction of neonatal sepsis have been reported 15,16…”
Section: Introductionmentioning
confidence: 99%